An Active Data Cube (ADCu)-Based Security Framework for Enhancing Security, Access Control, and Accountability in Cloud Computing Environments - Rohollahi, Aliakbar; Bagherifard, Karamollah; Malekhosini, Raziyeh (Management Strategies and Engineering Sciences, 2025)
Cloud computing, as a leading-edge technology, is rapidly expanding across critical sectors such as healthcare and banking due to its high scalability and flexibility. However, concerns related to data security and privacy preservation remain fundamental challenges that hinder the widespread adoption and full utilization of its benefits. This paper introduces the Active Data Cube (ADCu)-based security framework aimed at enhancing the level of security, enabling intelligent access management, and ensuring effective threat response in cloud computing environments. By integrating both active and passive data protection mechanisms, the framework comprises three core layers—core data protection, data security and control, and data operation management—offering a comprehensive and efficient structure for data monitoring, control, and protection. Laboratory evaluations, along with a case study in the healthcare domain, demonstrated that the ADCu framework can detect and mitigate over 90% of cyberattacks and improve threat response time by up to 30%. Furthermore, by incorporating active auditing and role-based access control systems, user trust and overall system security significantly increased. The findings highlight the high efficiency, scalability, and reliability of this framework, positioning it as an innovative and credible solution for data protection in cloud computing. It can serve as a scientific and practical foundation for future research and applications in this field.